Penataan Objek Wisata Tepian Muaro Batulangkai Dengan Pendekatan Arsitektur Organik - Nur Hafizhoh; Wahyu Hidayat; Mira Dharma Susilawaty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Tepian Muaro Batulangkai tourism object is a tourist attraction Located in Muara Jalai Village, Kampar Utara District, Kampar Regency. This tourism object has great potential to be developed because it has Green and natural beauty. Besides this, the Tepian Muaro Batulangkai is a place that people do Traditional ceremony before Ramadan that is called mandi Balimau. The design method used is the result of field survey, literature study, and empirical data. The designing process of Tepian Muaro Batulangkai tourism object arrangement focuses on water Recreation, cultural recreation and family recreation. The design theme used is Organic architecture which is an architecture that connects the environment and nature. The concept used in the Arrangement of the Muaro Batulangkai tourism object is Rubber Fruit which is one of the plants that is around the location and is a source of local economic community..keywords: Kampar, Tepian Muaro Batulangkai , Organic Architecture